Unlocking the Aquatic Ballet of Sea Turtles: Harnessing Sea Turtle Biomechanics for the Evolution of Marine Technologies - van der Geest, Nick (Auckland University of Technology, 2023)
Sea turtles are marvels of marine navigation, employing sophisticated biomechanical strategies that enable them to traverse thousands of kilometres across oceans. Despite their importance in oceanic ecosystems, all sea turtle species face the risk of extinction, largely due to human activities. This doctoral thesis provides an in-depth analysis of the biomechanics and hydrodynamics involved in sea turtle movement. It emphasises creating non-intrusive techniques for examining and mimicking their swimming behaviours. The study aims to enhance biological and biomechanical understanding and inspire technological innovations drawing from nature's design. This research first introduces a novel, non-invasive procedure for studying the biomechanics of wild sea turtles by utilising underwater drones to film them in their natural habitat, the Great Barrier Reef. Through this approach, distinctive swimming patterns were observed, deviating from those recorded in captive juveniles. Our findings show that the flipper goes through a closed-loop trajectory with extended sweeping of the flipper tip towards the centre of the carapace to create a clapping motion. We have named this the "sweep stroke", and in contrast to previously described four-stage models, it creates a five-stage cycle swimming locomotion model. Delving into the migratory prowess of sea turtles, the thesis then examines the biomechanical and hydrodynamic aspects of long-distance travel. Sea turtles achieve this remarkable feat despite a diet consisting primarily of low-energy foods. A model based on the green sea turtle (Chelonia mydas) and a custom testing rig was developed to investigate only the upstroke phase of their swimming. It was found that sea turtles likely utilise a passive upstroke, significantly reducing their drag coefficient and allowing them to maintain swim speed without generating thrust, thereby conserving energy. The thesis further investigates the green sea turtle's incredible ability to swim up to 50 km per day on a diet of seagrass or microalgae. By factoring in the newly described five-stage swimming cycle, a soft-robotic sea turtle named Cornelia, capable of mimicking the real animal's form and function, was developed to provide biomechanical insights without invasive experimentation. The study reveals that the green sea turtle may only produce propulsion for about 30% of the limb beat cycle, with the rest of the time spent in a low-drag glide, minimising speed loss due to their large mass and low drag coefficient. These insights can potentially revolutionise oceanic exploration through a new generation of robotic systems that harness sea turtle-inspired propulsion strategies. Furthermore, this work utilised Cornelia, to investigate the flow manipulation during the sea turtle's propulsive phase. By analysing the relationship between swim speed, flipper angle of attack, power consumption, and the production of thrust and lift, this research hypothesises how flow features contribute to the sea turtle's propulsive efforts and cost of transport. The findings indicate that sea turtles achieve exceptionally low cost of transport values, affirming the efficiency of their swimming technique and providing valuable data that could inform the design of high-efficiency underwater drones for extended missions. Lastly, the thesis explores the development of prosthetic flippers for sea turtles that have lost a limb. Robotic testing demonstrated that a prosthetic could effectively mimic the sea turtle's downstroke and upstroke, allowing for regained manoeuvrability. Swim tests with the prosthetic attached to the robotic model yielded promising results, nearly matching the average swim speeds of wild sea turtles. This work aspires to lay the groundwork for open source prosthetic designs that could empower veterinary professionals worldwide to assist injured turtles. The broader ambition is to inspire further animal-based robotic designs, advancing technologies geared towards ecological conservation and rehabilitation. In conclusion, this thesis presents a multifaceted investigation into the locomotion of sea turtles, yielding significant original insights that bridge biology, robotics, conservation, and bioinspired engineering. The findings have profound implications for understanding the biomechanical efficiency of these endangered species and offer a pathway toward developing sustainable technologies that could benefit both wildlife conservation and human engineering pursuits.